Single-Leg Vertical Hop Test Detects Greater Limb Asymmetries Than Horizontal Hop Tests After Anterior Cruciate Ligament Reconstruction in NCAA Division 1 Collegiate Athletes - Michael J Zarro (North American Sports Medicine Institute, 2021)
# Background